Economics of Recreational Ecosystem Services : Application of Individual Travel Cost Method from Nandi Hills Forest in Karnataka - Balasubramanian, M. (Indian Forester, 2023)
In the present paper the economic value of recreational services provided by Nandi Hills, Karnataka has been estimated at â‚¹ 2.47 billion for 2019. This study interviewed 150 tourist visitors, using a questionnaire method at the recreation site. The result of the study has found that more than 55 per cent of the respondents are willing to pay more than the existing entry fee at the recreation area. The main implications of the study are: first, development and investment opportunity for nature - based recreation areas; second, enhancing awareness of the ecosystem services; and three sustainable uses of ecosystem services at the local level.